Formulation And Evaluation Of Zolpidem Tartrate Extended Release Matrix Tablets - Karthikeyan, M (International Journal of Pharmaceutical & Biological Archive, 2011)
In the present study, to establish oral extended release tablets of Zolpidem tartrate using different polymers. The tablets were prepared using HydroxyPropyl Methylcellulose tartaric acid, cellulose, microcrystalline, lactose, anhydrous, magnesium stearate different polymers to impart extended release study. Tablets were evaluated by different parameters such as weight uniformity, content uniformity, thickness, hardness, IR spectral analysis, in vitro release studies, and kinetic analysis of dissolution data, stability studies and pharmacodynamic activity. The present study concludes that extended release tablets of zolpidem tartrate can be a good way to increases the dissolution and bioavailability of zolpidem tartrate and also showed significant anti-ulcer activity in rats.